Comparing trained student peers versus paid actors as standardized patients for simulated patient prescription counseling - Megan N. Willson; Kimberly C. McKeirnan; Andrew Yabusaki; Christina R. Buchman (Elsevier, 2021)
Background: Simulation can be a useful tool for teaching and assessing clinical skills, but can also be costly and faculty-time intensive. It is defined as a technique to create an activity to portray a real experience for purpose of practicing or evaluating. Simulations can use standardized patients (SPs), which can be paid actors (PASPs), staff and faculty, manikins, volunteers, or students from higher level cohorts, also known as advanced class standardized patients (ACSPs). Objective: The objective of this study was to conduct a multifaceted analysis comparing ACSPs and PASPs, based on student performance in the assessment, student preference of SP type, and SP performance as an actor. Methods: ACSPs and PASPs were used in a summative prescription counseling role play. For the evaluation, students counseled a SP about a new prescription medication and answered questions about taking an over-the-counter product with the new medication. The interaction was recorded and evaluated by faculty using a previously developed rubric. SP performance was evaluated by faculty using a separate rubric to determine how well the patient role was performed. A pre- and post-evaluation survey was completed by student pharmacists to gather student preferences about SPs and confidence in their counseling skills. Data were evaluated using a paired t-test. Results: One hundred sixty-seven student pharmacists completed the summative prescription counseling evaluation. Student pharmacists performed well overall with minimal differences between SP types. Students preferred PASPs to role play the patient but felt that the actor type did not affect their performance. Conclusions: ACSPs performed the role of the SP well for a summative prescription counseling session without impacting student performance compared to PASPs and with reduced cost. However, students preferred PASPs, and PASPs were better at role playing the patient.